Effects of Early Life Stress on Neuroendocrine and Neurobehavior: Mechanisms and Implications - Ming-Chi Lai; Li-Tung Huang (Pediatrics and Neonatology)
Evidence continues to mount that adverse experiences early in life have an impact on brain functions. Early life stress can program the development of the hypothalamic-pituitary-adrenal axis and cause alterations of neurochemistry and signaling pathways involved in regulating neuroplasticity, with resultant neurobehavioral changes. Early life experiences and genetic factors appear to interact in determining the individual vulnerability to mental health disorders. We reviewed the effects of early life stress on neuroendocrine regulation and the relevance to neurobehavioral development.